Implementasi Penawaran Produk Toko Online KPRI UNS Dengan Metode AHP TOPSIS - Agus Purbayu; Amar Abdurrafi Nur (Universitas Sebelas Maret, 2018)
Online store KPRI UNS Surakarta is a web-based information that is used to sell goods at the shop KPRI UNS Surakarta. Difficult in the sale of goods because there is no supply of goods in accordance with the criteria. So that the required in accordance with the criteria of members with AHP-TOPSIS method..The metodology conducted to design and make information system online shop KPRI UNS Surakarta is used waterfall metodology is data collection, the system analysis(determine the functional and non functional requirement), system design (erd, use case diagram, use case text, sequence diagram, and class diagram), and implementation (coding and testing). Information system online shop Online store information system KPRI UNS Surakarta is able to manage data and using it to offering product. This Offering help by Desission Suport Sistem which Method is AHP Topsis.